Banking and Insurance Recapitalization During the 2007–2009 Credit Crisis. (22nd September 2015) - Cybo‐Ottone, Alberto; Savorelli, Lorenzo
Abstract : This paper explores the feedback loop between the intensity of financial intermediary recapitalization and a number of measures of credit and liquidity risk. We cover the entire 2007–2009 subprime crisis with a sample that includes the 97 largest banks and insurance companies on both sides of the Atlantic. We model the intensity of recapitalization by implementing a scale measure inspired by the Corrective Action system used by U.S. banking regulators. The proposed ordering starts with inaction, followed by dividend cuts, to issues of new equity, to bailouts. Our risk measures include toxic asset exposures, credit default swap spreads, and Merton‐style probabilities of default. We show that there is a monotone relationship between the intensity of risk and the intensity of recapitalization across all firms and jurisdictions in the sample. We are able to simplify the large heterogeneity of regulations and business models across sectors and countries within a fairly simple and general classification scheme. This scheme distinguishes between individual bailouts, targeted at bankruptcy prevention, and more nuanced collective bailouts, which were more related to the prevention of systemic risk arising from potentially solvent institutions.